La contabilidad de gestión como aliada empresarial en las necesidades de los mercados actuales (Revista "Boletín el Conuco", 2020)
The present article is a product of thetheoretical frame of the research projectthat is related to the title of the same one. In known that accounting is an essential tool for organizations facilitates the development of administrative and operational processes, children who send the company a UN High staircase In a rapidly changing market; esta suit was characterized by changes said Jack Araujo (sf budgeted Barrios, Lemos de la Cruz and Fúquene, 2010) “The Message of accounting is multiple and has specialized” (p.165). Why is subdivided into accounting specializations in management accounting involves all manner conducive to the needs of an organization and says Rodriguez Zaá & De Freitas (2012) “accounting theory has been directly or indirectly changes, which only passes through recorder is one debits and credits until you find the present accounting system of the United Nations tailored to the needs of each organization “(p. 164).To carry out the project, the qualitative paradigm covering the interpretive study of UN publications related to the topic under study, found in the databases required indexed journals and repositories, of which the most important aspects It is made taking into account the fundamental elements that surround the project, the highlight of this form of management accounting that reflects in its financial statements management that occurs in the administration, which is more a result of positive or negative changes in productivity and competitiveness of SMEs.
Keywords: management accouting; strategic; management; stakeholders; make to decisions; information utility; productivity; efficiency